Experimental and numerical studies on punching shear strength of concrete slabs containing sintered fly ash aggregates - Babu B, Ranjith; R, Thenmozhi (Revista de la Construcción. Journal of Construction, 2021)
This paper presents experimental and numerical investigations on M30 Grade of concrete containing 40% of sintered fly ash aggregates (SFAs) on the punching behaviour of reinforced concrete (RC) slabs. Two 1000 x 1000 x 100 mm reinforced concrete slabs were cast and subjected to punching tests. The experimental results were compared with creating a nonlinear finite element programme using ABAQUS. This 3D Finite element analyses were performed with the appropriate modelling of element size and the constitutive modelling of concrete. The material parameters of the damaged plasticity model in ABAQUS were calibrated based on the test results of slab – plate connection. The comparison between experimental and numerical results indicates that the calibrated model correctly predicts the punching shear response of the slabs. A modification of 0.4 is introduced in MC2010 code.